2012
DOI: 10.1016/j.gie.2012.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pancreas in vivo using EUS spectrum analysis with electronic array echoendoscopes

Abstract: Background Spectral analysis of the radio-frequency (RF) signals that underlie grayscale EUS images has been used to provide quantitative, objective information about tissue histology. Objective Our purpose was to validate RF spectral analysis as a method to distinguish between chronic pancreatitis (CP) and pancreatic cancer (PC). Design & Setting A prospective study of eligible patients was conducted to analyze the RF data obtained using electronic-array echoendoscopes. Patients Pancreatic images were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Spectral analysis has been used in various applications, including characterization of plaque composition by intravascular ultrasound (IVUS) [16] , [17] , lesions induced by high intensity focused ultrasound (HIFU) [18] , [19] and RF ablation [20] . Spectral parameters have also shown the ability to identify changes in tissue state for prostate, breast, pancreas, lymph node, and other cancer types [21] , [22] , [23] , [24] , [25] , [26] , [27] . Oelze et al .…”
Section: Introductionmentioning
confidence: 99%
“…Spectral analysis has been used in various applications, including characterization of plaque composition by intravascular ultrasound (IVUS) [16] , [17] , lesions induced by high intensity focused ultrasound (HIFU) [18] , [19] and RF ablation [20] . Spectral parameters have also shown the ability to identify changes in tissue state for prostate, breast, pancreas, lymph node, and other cancer types [21] , [22] , [23] , [24] , [25] , [26] , [27] . Oelze et al .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, an objective evaluation of each variable using a digital image analysis would be necessary. Recently, many studies have been conducted along these lines[19,20]. Zhu et al[21] reported that digital image processing and computer-aided EUS image differentiation technologies are highly accurate and noninvasive in differential diagnosis between pancreatic cancer and chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the sensitivity and specificity for detecting pancreatic malignancies were 100% and 92.9% respectively[ 91 ]. Three-dimensional reconstruction and spectrum analysis using EUS has shown -good results, and has the potential to be used more often in the future[ 92 ].…”
Section: Novel Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…As pancreatic cancer has the potential to cause micro metastasis even in early stage of disease, research has been carried out to determine the molecular profiling of these tumors. Imaging agents such as peptides that bind to specific factors on the surface of pancreatic tumors have been developed and include: cathepsin E, integrin α v β 6 , plectin 1, claudin-4 and oncolytic adenovarirus mutant[ 92 - 97 ] . Similarly, engineered biological agents such as oncolytic adenovirus have shown efficacy and tumor selectivity in preclinical pancreatic cancer models[ 98 , 99 ].…”
Section: Novel Diagnostic Imaging Modalitiesmentioning
confidence: 99%